Cultural Transformation on Decision-Making for Indonesia’s 35,000 MW Electricity Mega Project: A Systems Thinking’s Perspective - Hendro, Dewo; Sunitiyoso, Yos (SBM ITB, 2016)
Abstract. The study aims to analyze the existing system situation of the project, to compare it with the ideal system situation, and to propose the intervention to close the gap between the two system situations. The analysis method used to map the situations is the causal loop diagram. The study combines primary data using interviews and secondary data analyses on literature, government regulations, reports, and related sources. The findings of the study suggest that an obstacle of the project completion which should be considered seriously is the legal uncertainty. Root causes of this problem are the ambiguity of decision makers' roles, bounded-awareness occurrence, and the influence of the hidden traps on decision-making. Therefore solutions are proposed to solve the situation and transform it into the ideal system situation: decision makers roles are clarified, every sector or stakeholder is able to see, seek, use, and share integrated information properly, and every efficient decision made is implemented appropriately into actions.Keywords: decision-making, bounded awareness, hidden traps, integrated system, legal uncertainly, mega-projectAbstrak. Studi ini bertujuan untuk melakukan analisis situasi sistem proyek saat ini, membandingkannya dengan situasi sistem yang ideal, dan untuk mengusulkan intervensi untuk menutup kesenjangan antara dua situasi tersebut. Metode analisis yang digunakan untuk memetakan situasi adalah diagram sebab-akibat. Studi ini menggunakan kombinasi data primer mengunakan interview dan data sekunder dari literature, peraturan pemerintah, laporan dan sumber terkait. Hasil studi ini menyarankan mengenai suatu kendala penyelesaian proyek yang harus dipertimbangkan secara serious yaitu ketidakpastian hukum. Akar penyebabnya adalah ambiguitas peran pengambil keputusan, terjadinya keterbatasan kesadaran, dan pengaruh perangkap tersembunyi pada pengambilan keputusan. Oleh karena solusi-solusi diusulkan untuk mengatasi situasi dan mengubahnya menjadi situasi sistem yang ideal yaitu: peran pengambil keputusan yang diklarifikasi, setiap sektor atau pemangku kepentingan mampu melihat, mencari, menggunakan, dan berbagi informasi terintegrasi dengan benar, dan setiap keputusan yang efisien diimplementasikan dengan tepat ke dalam tindakan.Kata kunci: pengambilan keputusan, keterbatasan kesadaran, perangkap tersembunyi, sistem terintegrasi, ketidakpastian hukum, mega-proyek.